2014
DOI: 10.4336/2014.pfb.34.78.657
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade da madeira e do carvão vegetal oriundos de floresta plantada em Minas Gerais

Abstract: Resumo-O objetivo deste trabalho foi avaliar a qualidade da madeira e do carvão vegetal oriundos de árvores jovens de Eucalyptus spp., bem como verificar a influência da idade e clone no desempenho energético desses combustíveis. Foram amostrados os clones 1277 e 0321 de Eucalyptus spp. em duas idades (46 e 58 meses). Na madeira foram determinadas as características químicas moleculares e elementares, a densidade básica, os estoques de carbono e lignina por volume, as densidades energéticas e os poderes calorí… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
2
16

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 18 publications
2
7
2
16
Order By: Relevance
“…A significant effect of species was observed for the contents of volatile materials and ash. The small variation between charcoal characteristics is related to the low influence of species over these properties and is explained by the fact that the ), EXT = total extractive content (%), LIG = insoluble lignin content (%), HOLO = holocellulose content (%), Ash = ash content (%) final carbonisation temperature was constant, which was also found by Protásio et al (2013Protásio et al ( , 2014.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…A significant effect of species was observed for the contents of volatile materials and ash. The small variation between charcoal characteristics is related to the low influence of species over these properties and is explained by the fact that the ), EXT = total extractive content (%), LIG = insoluble lignin content (%), HOLO = holocellulose content (%), Ash = ash content (%) final carbonisation temperature was constant, which was also found by Protásio et al (2013Protásio et al ( , 2014.…”
Section: Resultssupporting
confidence: 63%
“…The small variation between charcoal characteristics is related to the low influence of species over these properties, and the final carbonisation temperature was constant, as also found by Protásio et al (2013Protásio et al ( , 2014. In a study with 7-year-old E. urophylla, Reis et al (2012) found average ash contents of less than 0.81% and maximum content of volatile materials, 74.46%.…”
Section: Resultssupporting
confidence: 58%
“…The main application traditionally given to wood around the world is combustion for energy production due to its high-productive and renewable potential. Wood combustion accounts for more than half of the forest biomass consumed worldwide, mainly in developing countries, such as Brazil (Moreira, 2011), which is the largest charcoal producer in the world (Protásio et al, 2014). In Brazil, the increase of areas planted with "energy forestry" makes its energy matrix environmentally healthier due to the replacement of fossil fuels by renewable energy sources; moreover, this matrix is socially fair because of the large number of job positions generated by investments in the sector (Moreira, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Isso porque, para esta destinação são desejáveis madeiras com baixos teores de minerais, já que estes podem se constituir em contaminantes e, quando se acumulam no processo são causadores de corrosão, de erosão e de entupimentos, levando à redução da vida útil dos materiais e perdas de produção, principalmente, em fábricas com ciclo de água mais fechado (FREDDO, 1997). No entanto, há que se estudar os teores de cinzas em indivíduos No caso das plantas de T. grandis, os valores para a relação C/N foram semelhantes aos obtidos por Santana (2009) e Protásio et al (2014). Considerando que a relação C/N afeta diretamente o tempo de degradação do material vegetal, esta pode indicar que o teor inicial de lignina presente nas plantas de T. grandis e, consequentemente, sua maior dificuldade na degradação por fungos pode ser aumentada com a adubação de plantio.…”
Section: Tratamentounclassified